The complete art of war - Sunzi 6th cent. B.C; Clausewitz, Carl von 1780-1831; Machiavelli, Niccolò 1469-1527; Jomini, Antoine Henri baron de 1779-1869 (Wilder Publications, 2008)
This is the most important book ever written about warfare and conflict. Lionel Giles' translation is the definitive edition and his commentary is indispensable. The Art of War can be used and adapted in every facet of your life. This book explains when and how to go to war, as well as when not to. Learn how to win any conflict whether it be on the battlefield or in the boardroom.